La variante léxica pelucón en Ecuador: un análisis del discurso mediado por computadora (Ensayos) - Mejía, Santiago (2022)
The article investigates the pelucón lexical variant in the Ecuadorian context, based on the methodology called computer-mediated discourse analysis. More than thirty web pages in which the variant appeared, and which were published between 2007 and 2020, were analyzed in order to identify their predominant meanings, and then an analysis was carried out from pragmatics, discourse analysis and studies of populism. It is concluded that there are two dominant meanings in the network: the rhetoric of discord and the rhetoric of meritocracy. The first seeks to open a communicative conflict with the elites, while establishing an identity horizon with disadvantaged groups. The second is the response of the wealthy or conservative groups, when they feel questioned by the pointing out of the lack of legitimacy of their status.